1.d2y/dx2-2dy/dx+5y=extan2x
2.dy/dx+3y=3x2e-3x
1."{d^2y\\over dx^2}-2{dy\\over dx}+5y=e^xtan2x"
The differential equation has the form
"{d^2y\\over dx^2}+p{dy\\over dx}+qy=s" where "p=-2" , "q=5" and "s=-e^xtan2x"
Solve corresponding homogenous linear equation
"{d^2y\\over dx^2}+p{dy\\over dx}+qy=0"
Its characteristic equation is given as
"q+(k^2+kp)=0\\implies5+(k^2-2k)=0 \\implies k^2-2k+5=0"
"\\therefore" "k_1=1-2i" and "k_2=1+2i"
"\\implies" "y=C_1e^{k_1x}+C_2e^{k_2x}=C_1e^{(1-2i)x}+C_2e^{(1+2i)x}"
Solve the inhomogeneous equation
"{d^2y\\over dx^2}+p{dy\\over dx}+qy=s"
By use of variation of parameters method, suppose that "C_1" and "C_2" are functions of "x"
"\\therefore" The general solution is
"y=C_1(x)e^{(1-2i)x}+C_2(x)e^{(1+2i)x}"
To find "C_1(x)" and "C_2 (x)" ,by the method of variation of parameters ,we find the solution from the system:
"y_1(x){d\\over dx}C_1(x)+y_2(x){d\\over dx}C_2(x)=0"
"{d\\over dx}C_1(x){d\\over dx}y_1(x)+{d\\over dx}C_2(x){d\\over dx}y_2(x)=f(x)"
Where "y_1(x)" and "y_2(x)" are linearly independent particular solutions of linear ordinary differential Equations
"y_1(x)=e^{x(1-2i)}" , "C_1=1" and "C_2=0"
"y_2(x)=e^{x(1+2i)}" , "C_1=0" and "C_2=1"
And the free term is given as
"f(x)=e^xtan(2x)"
So the system has the form:
"e^{x(1-2i)}{d\\over dx}C_1(x)+e^{x(1+2i)}{d\\over dx}C_2(x)=0"
"{d\\over dx}C_1(x){d\\over dx}e^{x(1-2i)}+{d\\over dx}C_2(x){d\\over dx}e^{x(1+2i)}=e^xtan(2x)"
solving the system gives
"{d\\over dx}C_1(x)={ie^{2ixtan(2x)}\\over 4} \\implies C_1(x)=\\int{ie^{2ixtan(2x)}\\over 4}dx"
"{d\\over dx}C_2(x)={ie^{-2ixtan(2x)}\\over 4}\\implies C_2(x)=-\\int {ie^{-2ixtan(2x)}\\over 4}dx"
Evaluate "\\int{ie^{2ixtan(2x)}\\over 4}dx={log(e^{2ix}-i)\\over 8}-{log(e^{2ix}+i)\\over 8}-{ie^{2ix}\\over 8}"
"-\\int{ie^{-2ixtan(2x)}\\over 4}dx={log(e^{2ix}-i)\\over 8}-{log(e^{2ix}+i)\\over 8}+{ie^{2ix}\\over 8}"
Substitute "C_1(x)" and "C_2(x)" to
"y=C_1(x)e^{(1-2i)x}+C_2(x)e^{(1+2i)x}"
"\\implies y=({log(e^{2ix}-i)\\over 8}-{log(e^{2ix}+i)\\over 8}-{ie^{2ix}\\over 8})e^{(1-2i)x}+({log(e^{2ix}-i)\\over 8}-{log(e^{2ix}+i)\\over 8}+{ie^{2ix}\\over 8})e^{(1+2i)x}"
"\\therefore y=(C_2sin(2x)+(C_1+{log(sin(2x)-1)\\over 8}-{log(sin(2x)+1)\\over 8})cos(2x)e^x"
2."{dy\\over dx}+3y=3x^2e^{-3x}"
This differential equation has the form
"{dy\\over dx}+p(x)y=Q(x)"
Solve the correspondent linear homogenous equation
"{dy\\over dx}+p(x)y=0" where "p(x)=3" and "Q(x)=3x^2e^{-3x}"
"\\implies {dy\\over dx}=-p(x)y \\implies {dy\\over y}=-p(x)dx \\implies \\int{1\\over y}dy =-\\int p(x)dx"
"\\therefore log(|y|)=-\\int p(x)dx \\implies |y|=e^{-\\int p(x)dx}"
"\\implies y_1=e^{-\\int p(x)dx}=e^{-\\int 3dx}=e^{C_1-3x}"
and "y_2=-e^{-\\int p(x)dx}=-e^{-\\int 3dx}=-e^{C_2-3x}"
This leads to correspondent solution for any constant C not equal to zero
"y=Ce^{-3x}"
Now we should solve the inhomogeneous equation
"{dy\\over dx}+p(x)y=Q(x)"
Use variation of parameters method by considering C as a function of x
"y=C(x)e^{-3x}"
Apply it in the original equation using rules for product differentiation of composite functions derivative .We find that
"{d\\over dx}C(x)=Q(x)e^{\\int p(x)dx}"
Let use Q(x) and p(x) for this equation, we get the first order differential equation for C(x)
"{d\\over dx}C(x)=3x^3 \\implies C(x)=\\int3x^2dx=x^3+c"
use C(x) at
"y=C(x)e^{-3x}"
"\\therefore" "y=(C_1+x^3)e^{-3x}"
Comments
Leave a comment